Pemasaran Digital Dalam Kewirausahaan - Decky Hendarsyah (Iqtishaduna: Jurnal Ilmiah Ekonomi Kita)
This paper aims to discuss the concepts and new ideas, opportunities and challenges of digital marketing in entrepreneurship. After discussion, it was found that digital marketing has a very close relationship with entrepreneurship, where both items have the same target. Then digital marketing is part of entrepreneurial activities. Digital marketing has huge opportunities in the development of the business world from now until in the future where the target market has been transformed into a digital platform. While the challenges that must be faced by the business world when implementing digital marketing are readiness in terms of human resources and financial resources in supporting digital marketing activities.